A PRIMARY SCHOOL PUPIL'S SCHOOL BAG - Živorad Marković; Dragoljub Višnjić; Milovan Stamatović; Goran Šekeljić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
There are more researches which deal with the ratio between body weight and school bag which in most cases on all continents overpasses the weight of 10% of pupils' total weight, which indicates that recommendations of World Health Organization are not followed. World Health Organization proposed that maximal weight which could be carried by children should not be higher than 10% of their body weight. The weight of a school bag that children carry to school every day is from 4.0 to 7.7 kilos in different researches (Casey & Dockrell, 1996; Pascoe et al.; Grimmer et al., 1999). Represented by percentage of children's body weight these values vary from 10% to 20%. The goal of this research was to study the relations between pupils' body weight and school bag weight and on the basis of the results to give recommendation for praxis. The results for younger and older pupils are similar to the results of other researches in the world. The concern is about the great gap which goes even further in higher classes, which indicates the relation to school of some pupils.